Development and implememtation of new UK national guidance for preventing and managing cardiac events during trastuzumab treatment. (22nd September 2015) - Plummer, CJ; Barlow, M; Jones, AL; Verrill, MW; Barrett-Lee, PJ; Canney, PA; Gilmour, I; Wardley, AM; Robb, SD
Abstract : Background: Cancer treatment has changed significantly over the past decade, resulting in a marked improvements in survival rates. This has been achieved with the use of more intensive regimens and most recently, new "targeted" biological agents. The heart is uniquely vulnerable to short and long-term side-effects of cancer treatment and it is important that cardiologists are aware of the implications of these. Treatment with trastuzumab (Herceptin), an antibody directed against the extracellular HER2 receptor, which is overexpressed in 15–20% of breast cancers, has significantly improved disease-free survival but is associated with a functional, reversible cardiomyopathy. Current clinical guidelines for identifying and managing cardiac events with this agent were taken directly from clinical trial protocols and are not suited to use in routine clinical practice: They require a precision in the measurement of left ventricular ejection fraction that is not achievable in routine practice. They include very precautionary exclusion criteria and stopping rules such that some women who may safely benefit from trastuzumab without long-term adverse cardiac sequelae do not receive it, or do not complete a full course of HER2-targeted therapy. Finally, they do not include a proactive approach to the prevention or treatment of cardiomyopathy. Conclusions: The guidelines have been peer-reviewed and endorsed by the National Cancer Research Institute. They are being implemented in the centres participating in the development of these guidelines and this is being audited for safety and treatment completion. The principles of this approach may be applicable to other cancer treatment with cardiac side effects.